GENETIC CHARACTERIZATION AND PERFORMANCE EVALUATION OF ELITE COTTON STRAINS FOR MORPHOLOGICAL AND PHYSIO-CHEMICAL TRAITS UNDER HEAT STRESS CONDITIONS - HUSSAIN , S; KHAN , MM; TALIB , I; KHALID , M; ZUBAIR , M; MURTAZA , G; AKHTAR , I; QAMAR , MJ; FAROOQ , MR; ASHFAQ , M; et al. (Biological and Clinical Sciences Research Journal, 2024)
One of the key steps in developing heat-tolerant, climate-smart cotton genotypes is evaluating and screening available cultivated germplasm. The current study was designed to evaluate the key cotton strains developed for release in heat-prone areas of Punjab and Pakistan. Thirteen cotton strains, along with check variety BH-184, were sown under randomized complete block design (RCBD) in triplicates. The plant-to-plant and row-to-row distances were maintained at 30 cm and 70 cm, respectively. The results revealed the presence of highly significant variations among cotton strains for studied plant traits in 13 cotton strains. Correlation analysis unveiled the presence of highly significant and positive correlation of seed cotton yield with net photosynthetic rate (r = 0.982**), total chlorophyll contents (r = 0.976**), superoxide dismutase (r = 0.966**), bolls per plant (r = 0.786**), nodes per plant (r = 0.683**), plant height (r = 0.653**) and sympodia per plant (r = 0.623**) while strong negative correlation with superoxide dismutase (r = -0.952**). Cluster, principal component and biplot analysis classify cotton strains into groups based on their performance under heat stress conditions. These analyses verified the results obtained through correlations and further revealed that net photosynthetic rate, total chlorophyll contents, superoxide dismutase, plant height and sympodia per plant and superoxide dismutase were the most divergent traits and must be considered in developing a scheme to develop heat-tolerant cotton genotypes.